The use of nano composites in automotive applications - Lu, Y. Charles; Pilla, Srikanth (SAE International., 2016)
With their high specific strength and stiffness, composites have the potential to signicantly lower the vehicle weight, which can have a dramatic effect on improving fuel efficiency and reducing greenhouse gas emission. This book consists of a collection of technical papers selected from the automotive composites and other relevant sessions that the editors have organised for the SAE World Congress over the past decade.